2023
DOI: 10.1101/2023.10.11.554933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of hippocampal noninvasive theta-burst stimulation on consolidation of associative memory in healthy older adults

Traian Popa,
Elena Beanato,
Maximilian J. Wessel
et al.

Abstract: Stimulation of deep brain areas can offer benefits against cognitive impairments associated with aging. So far, this was only possible via invasive methods accompanied by risks. Grossman et al. proposed a new noninvasive stimulation technique, transcranial temporal interference electric stimulation (tTIS), which can be steered to target and modulate activity of deep brain structures. Memory capacity depends on subcortical structures such as the hippocampus, hence, modulation of hippocampal activity could benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…This result is also in line with a previous in vivo study that reported hippocampal TIS to improve associative memory 24 hours after stimulation, but not earlier, after 90 minutes (Δf = 5 Hz). 11 Burst durations, spikes in bursts, BSRs, and ISI in bursts remained unchanged for all the stimulation conditions 24 hours after the stimulation (Fig. 6C-F and H).…”
Section: Electrical Stimulation Of Neurons In Vitromentioning
confidence: 82%
See 3 more Smart Citations
“…This result is also in line with a previous in vivo study that reported hippocampal TIS to improve associative memory 24 hours after stimulation, but not earlier, after 90 minutes (Δf = 5 Hz). 11 Burst durations, spikes in bursts, BSRs, and ISI in bursts remained unchanged for all the stimulation conditions 24 hours after the stimulation (Fig. 6C-F and H).…”
Section: Electrical Stimulation Of Neurons In Vitromentioning
confidence: 82%
“…6 TIS has been reported to cause minimal side effects and high tolerability. [7][8][9][10] Previously, TIS at theta or gamma frequency envelopes has been used to modulate brain activity in the hippocampus, 6,8,11 striatum, 8,12 and motor cortex, 7,9 demonstrating a targeted stimulation with minimal exposure to overlying brain areas. 6,12 Specifically, theta-frequency TIS has been shown to modulate hippocampal activity, enhance memory performance, 6,11 and alter functional connectivity after TIS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations